Evaluation of Synthetic Poison and Biological Pesticides against Diaphorina citri in Citrus in Dir (Journal of Agriculture and Biology, 2025)
On Diaphorina citri in 2020 at Citrus Orchard, Rabbat District Dir Lower, this study was performed to assess the impacts of extract of neem seeds artificial insecticides and bio-pesticides on Diaphorina citri in 2020. The study comprised five procedures: extract of neem seed, bifenthrin, cypermethrin, a control group along with indoxacarb. This study utilised a randomised complete block design (RCBD). In a citrus orchard, a total of 5 samples were selected, and every plant was partitioned into four different sections. From each branch, five leaves were collected. This finding demonstrated that synthesized insecticides offered more rapid and efficient control than herbal extract, that exhibited a slower response. In the experiment, indoxacarb, cypermethrin, neem seed extract, and also bifenthrin were applied administered to combat Citrus psylla, while the remaining control plants remained untreated for comparative purposes. The results indicated that, among all tested chemicals, bifenthrin was efficient in control of pest, accompanied by cypermethrin, neem seed botanical extract, and indoxacarb. The experiment further validated the superior performance of bifenthrin compared to the herbal extract.